2019
DOI: 10.1002/ijc.32661
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between protein biomarkers of chemotherapy response and microsatellite status, tumor mutational burden and PD‐L1 expression in cancer patients

Abstract: Chemotherapy and checkpoint inhibitor immunotherapies are increasingly used in combinations. We determined associations between the presence of anti‐PD‐1/PD‐L1 therapeutic biomarkers and protein markers of potential chemotherapy response. Data were extracted from a clinical‐grade testing database (Caris Life Sciences; February 2015 through November 2017): immunotherapy response markers (microsatellite instability‐high [MSI‐H], tumor mutational burden‐high [TMB‐H], and PD‐L1 protein expression) and protein chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 51 publications
(216 reference statements)
1
23
0
Order By: Relevance
“…A recent review reported that PD-L1 is not a reliable predictive biomarker for ICBT in RCC [44]. In the present study, immunohistochemistry showed TUBB3 expression to be correlated with PD-L1 expression in ccRCC, which is consistent with a previous study [26]. However, the mechanism of correlation between TUBB3 and PD-L1 expression has not been fully elucidated.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A recent review reported that PD-L1 is not a reliable predictive biomarker for ICBT in RCC [44]. In the present study, immunohistochemistry showed TUBB3 expression to be correlated with PD-L1 expression in ccRCC, which is consistent with a previous study [26]. However, the mechanism of correlation between TUBB3 and PD-L1 expression has not been fully elucidated.…”
Section: Discussionsupporting
confidence: 88%
“…A recent report showed that TUBB3 expression is associated with PD-L1 expression in RCC, using immunohistochemistry [26]. However, evaluation of PD-L1 expression by immunohistochemistry is complicated due to many factors [27].…”
Section: Association Between Tubb3 and Pd-l1 In Ccrccmentioning
confidence: 99%
“…A single patient in our cohort was included in a basket trial with Pembrolizumab without clinical benefit and a later tumor sample analysis revealed no PD‐L1 positivity, but HER2 amplification was detected and Herceptin therapy was initiated (data not shown). Interestingly, one of the TOP2A ‐amplified cases also exhibited PD‐L1 positivity in IC giving a potential for combination chemotherapy with immune checkpoint inhibitors …”
Section: Discussionmentioning
confidence: 99%
“…Early findings by researchers showed that most of the MSI cases are sporadic colorectal cancer, which is caused by epigenetic inactivation of gene expression in offspring on account of the methylation of hMLH1 promoter without the gene mutation. Lynch syndrome is an autosomal dominant tumor syndrome caused by mutations in MMR strains, and it can also cause tumors in other parts of the colon and rectum [4].…”
Section: Introductionmentioning
confidence: 99%